Charting the development of a global market for low-carbon hydrogen - Max Schönfisch (Institute of Energy Economics at the University of Cologne (EWI), 2022)
This paper analyses the impact of supply technology choices and costs on structures and prices on the emerging low-carbon hydrogen market using a novel, integrated natural gas and hydrogen market model. It shows that natural gas-based low-carbon hydrogen production pathways predominate in technology-neutral scenarios in 2050. In scenarios where hydrogen production is gas-based, hydrogen is produced close to the point of consumption. Natural gas prices determine local hydrogen prices. In scenarios characterised by high shares of RES-based low-carbon hydrogen production, long-distance, cross-border trade in pure hydrogen becomes an economically viable proposition due to the heterogeneous distribution of low-cost RES potentials and significant hydrogen price spreads between countries with high hydrogen demand but poor RES potentials, and countries that are well endowed with cost-competitive RES. Trade is conducted almost exclusively via pipeline. The analysis finds the most significant potential for cross-border trade in and around Europe. It suggests that it would be economical for Europe to import substantial quantities of low-carbon hydrogen from North Africa.
Keywords: Q40; Q42; Q49; 330; Hydrogen